2014
DOI: 10.1007/s10545-014-9766-8
|View full text |Cite
|
Sign up to set email alerts
|

Large animal models and new therapies for glycogen storage disease

Abstract: Glycogen storage diseases (GSD), a unique category of inherited metabolic disorders, were first described early in the 20th century. Since then, the biochemical and genetic bases of these disorders have been determined, and an increasing number of animal models for GSD have become available. At least 7 large mammalian models have been developed for laboratory research on GSDs. These models have facilitated the development of new therapies, including gene therapy, which are undergoing clinical translation. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…20-22 And nowadays, gene therapy for GSD is studied more and more in animal models, and it shows the possibility to figure out the pathophysiology of hepatic adenoma and HCC development in GSD and also the possibility of important role for the treatment of GSD. 23 Little is known about HCC occurrence in patients with GSD, and, to our knowledge, there has been no cohort study about the incidence rate of HCC from hepatic adenoma in patients with GSD, except for a few case series. One case series study reported an incidence of HCC from hepatic adenoma of 11% (4 of 36).…”
Section: Hepatic Adenoma In Glycogen Storage Diseasementioning
confidence: 99%
“…20-22 And nowadays, gene therapy for GSD is studied more and more in animal models, and it shows the possibility to figure out the pathophysiology of hepatic adenoma and HCC development in GSD and also the possibility of important role for the treatment of GSD. 23 Little is known about HCC occurrence in patients with GSD, and, to our knowledge, there has been no cohort study about the incidence rate of HCC from hepatic adenoma in patients with GSD, except for a few case series. One case series study reported an incidence of HCC from hepatic adenoma of 11% (4 of 36).…”
Section: Hepatic Adenoma In Glycogen Storage Diseasementioning
confidence: 99%
“…By contrast, in the McArdle bovine and ovine models, muscle glycogen concentrations are 1.6 and 2.2 times higher, respectively, than in control animals [ 46 , 88 ]. In this regard, large animals such as cows and sheep represent better models to reproduce disease phenotypes than small models, as they show similarities with regard to humans in organ and body size, muscle bulk, and overall physio-pathological and metabolic characteristics [ 89 ]. In particular, the ovine model presents a body and muscle mass throughout life that is similar to humans [ 74 ].…”
Section: Critical Discussionmentioning
confidence: 99%
“…On the other hand, large animal models present similar glycogen levels to GSD patients, e.g., the McArdle ovine model glycogen levels are 2–5 times higher than WT cows [ 257 ]. Overall, sheep, cattle or horses (5 out of 15 of naturally-occurring GSD models) constitute a better model to reproduce human disease phenotypes than small models such as quails, cats and dogs (the remaining 10 out of 15 naturally-occurring GSD models) or rodents (25 out of 26 genetically modified GSD models), as they present closer similarities in organs and body size, muscle bulk and overall physio-pathologic and metabolic characteristics [ 258 ]. However, there are intrinsic difficulties in working with large animal models compared with small models, such as manipulation, phenotype characterization (e.g., exercise testing), breeding, housing costs and space availability, and the capacity to be shared among different research groups.…”
Section: Critical Discussionmentioning
confidence: 99%